Accessible Cinema for Older Adults: Can an App for Blind Viewers Benefit the Sighted Population? - Szkriba, Sonia (Journal of Audiovisual Translation, 2022)
Age-related sensory and cognitive decline of older adults is typically not taken into consideration while designing accessible audiovisual services. As most studies on audiovisual translation (AVT) and media accessibility have focused on young or adult audiences, we know little about specific preferences and needs of older adults regarding AVT. In 2015, 82% of Polish older adults declared that they never or almost never go to the cinema, which for the vast majority of foreign films offers subtitling. A study carried out as part of the AudioMovie project in Poland suggested that older adults may have problems with reading subtitles and that they are willing to use an accessibility application to watch films with audio subtitles (AST) in the cinemas. However, we still do not know if they are able to deal with the technology once they actually start using it. This focus group study investigated whether older adults experience problems with reading subtitles and whether they be willing to use a smartphone application in the cinema. The results show that older adults may have problems with following subtitles, especially when watching fast-paced films, and, although they are not always proficient smartphone users, the overall reception of the app was positive. Lay summary In Poland, the translation of foreign films in cinemas is usually provided through subtitling (dubbing is used only for family films). This mode of audiovisual translation might be particularly difficult to process for older viewers who usually experience vision loss, hearing loss and decline in cognitive functioning. While most academic studies have focused on young or adult audiences, little is known about the specific preferences and needs of older adults regarding the type of audiovisual translation. A survey carried out in Poland in 2018 has suggested that older adults may find it difficult to read subtitles and that they may be willing to use a smartphone application that would provide an oral translation (voice-over or dubbing) in cinemas. However, it is not yet known if this group of viewers is prepared to manage the functions of the technology (in this case, a smartphone) once they start using it. With that in mind, I conducted a group interview which investigated whether older adults experience problems with reading subtitles, and whether they would be willing to use a smartphone application in the cinema. The results show that older adults may have problems reading subtitles, especially when watching fast-paced films. The overall reception of the app was positive, though the participants were not always proficient smartphone users. The study also suggests that such applications could help elderly cinema-goers watch films in their preferred types of translation (such as dubbing or voice-over).